Ryzyko w decyzjach inwestycyjnych - Siewiera, Agnieszka (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
There is a risk involved in any investment project, and the more distant is the project in the future, the higher is the risk. The risk analysis forms an important part of the economical and financial analysis, and essentially supplements the financial evaluation of the project and the assessment of its effectiveness. Even if the investment is profitable, the risk involved may be too high. An investor ought to foresee the potential losses and determine the risk level acceptable for the owner of a project and all the parties involved. For the investor, the level of investment's effectiveness is the most important criterion by witch he makes the final decision about starting the project. The project will be undertaken, when its return rate is satisfying for the investor, especially in comparison with other alternative possibilities. Return rate has to include appropriate bonus for the risk involved in the project. This bonus has a form of the return rate's growth, convincing the investor to undertake the project with given probability of failure. A project with high risk factor ought to bring a higher return rate and a bigger bonus for risk. It is also important, that the more cautious and less willing to take risk is the investor, the bigger is the bonus he expects to get in return. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 371-378